Effects of 2% Dehydration on Lactate Concentration During Constant-Load Cycling. Issue 7 (July 2018) - Green, James M.; Miller, Brandon; Simpson, Jeffrey; Dubroc, Danielle; Keyes, Anthony; Neal, Kailee; Gann, Josh; Andre, Tom
Abstract : Abstract: Green, JM, Miller, B, Simpson, J, Dubroc, D, Keyes, A, Neal, K, Gann, J, and Andre, T. Effects of 2% dehydration on lactate concentration during constant-load cycling. J Strength Cond Res 32(7): 2066–2071, 2018—The lactate [La] threshold (LT) can predict endurance performance potential. Dehydration may alter LT. This study examined effects of dehydration on [La] response during constant-load cycling. Recreationally fit (V[Combining Dot Above]O2 peak = 48.7 ± 5.2 ml·kg −1 ·min −1 ) male participants ( n = 9) completed 2 × 40-minute constant-load cycling trials; euhydrated (HYD) and after previous evening passive (water bath) dehydration (2% body weight, DEH) (HYD and DEH counterbalanced). Lactate, heart rate (HR), 10-point Omni ratings of perceived exertion (RPE), and rectal temperature (Trec) were measured after warm-up (WU) and at 10, 20, 30, and 40 minutes. Before cycling, urine specific gravity (USG) was measured and participants estimated perceived recovery status (PRS). Urine specific gravity DEH (1.027 ± 0.004) was significantly greater than HYD (1.013 ± 0.007). After WU, [La] was significantly greater (all time points) for DEH (∼4.1 mmol·L −1 ) vs. HYD (∼3.5 mmol·L −1 ) with similar results for HR (DEH: ∼167, HYD: ∼158 b·min −1 ). For DEH, RPE was significantly greater (∼1 unit) at 20, 30, and 40 minutes, and Trec was significantly greater at 30 and 40 minutes (∼0.4° C). DEH (vs. HYD) also resulted in significantly different resting HR (93 ± 6, vs. 85 ± 7 b·min −1 ), significantly greater session RPE (7.7 ± 1.1 vs. 5.3 ± 1.1), and significantly lower subjective feelings of recovery (PRS = 6.4 ± 2.9, vs. 9.0 ± 1.5). Current results indicate systematic changes in [La] and associated physiological responses result from previous day dehydration. Hydration status should be a concern in paradigms where [La] assessment is used.